Dynamically frequency‐tunable and environmentally stable microwave absorbers - Xiao Liu; Lihong Wu; Jun Liu; Haiming Lv; Pengpeng Mou; Shaohua Shi; Lei Yu; Gengping Wan; Guizhen Wang (Carbon Energy)
Abstract The threat to information security from electromagnetic pollution has sparked widespread interest in the development of microwave absorption materials (MAMs). Although considerable progress has been made in high‐performance MAMs, little attention was paid to their absorption frequency regulation to respond to variable input frequencies and their stability and durability to cope with complex environments. Here, a highly compressible polyimide‐packaging carbon nanocoils/carbon foam (PI@CNCs/CF) fabricated by a facile vacuum impregnation method is reported to be used as a dynamically frequency‐tunable and environmentally stable microwave absorber. PI@CNCs/CF exhibits good structural stability and mechanical properties, which allows precise absorption frequency tuning by simply changing its compression ratio. For the first time, the tunable effective absorption bandwidth can cover the whole test frequency band (2−18 GHz) with the broadest effective absorption bandwidth of 10.8 GHz and the minimum reflection loss of −60.5 dB. Moreover, PI@CNCs/CF possesses excellent heat insulation, infrared stealth, self‐cleaning, flame retardant, and acid‐alkali corrosion resistance, which endows it high reliability even under various harsh environments and repeated compression testing. The frequency‐tunable mechanism is elucidated by combining experiment and simulation results, possibly guiding in designing dynamically frequency‐tunable MAMs with good environmental stability in the future.